Formulation and Evaluation of Sodium Alginate and Guar Gum Based Glycyrrhizin Loaded Mucoadhesive Microspheres for Management of Peptic Ulcer - Harwansh, Ranjit Kumar; Deshmukh, Rohitas (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Glycyrrhizin (GZ) is a bioactive ingredient of Glycyrrhiza glabra, reported for various therapeutic effects including gastro-protection. It has been associated with low absorption, early elimination, short half-life and poor bioavailability. Objectives: Aim of the current study was to formulate GZ loaded mucoadhesive microspheres by using mucopolymers like sodium alginate and guar gum for the management of peptic ulcer. Methods: Various GZ loaded microspheres (GZ-MS1-3) were prepared by an emulsification-crosslinking technique. These formulations were developed with different proportions of guar gum and sodium alginate. The formulations were characterized and evaluated by various parameters including particle size, zeta potential, entrapment efficiency (% EE), % yield, SEM, FTIR, swelling index, mucoadhesive efficiency, in vitro drug release and in vivo antioxidant activities. Results: Result stated that suitable particle size (50.18 ± 1.15 µm), zeta potential (-31.12 ± 2.16 mV), %EE (92.67 ± 1.91) and % yield (97.45 ± 1.83) was achieved with optimized formulation, GZ-MS1. Significant (***P<0.001) swelling index (0.94 ± 0.04) and mucoadhesive efficiency (95.98 ± 3.62%) was obtained with GZ-MS1. GZ-MS1 showed maximum drug release profile (94.57 ± 4.03 %) in simulated gastric fluid (SGF, pH 1.2) at 37 ± 0.5°C for 24 h. FTIR study confirmed that there was no interaction observed between GZ and excipients. Conclusion: Sustained release profile of the optimized formulation was achieved due to significant mucoadhesive efficiency of the sodium alginate and guar gum. Thus, the mucoadhesive microspheres of GZ would be an effective strategy for the management of peptic ulcer.
Keywords: Mucoadhesive microspheres; Glycyrrhizin; Mucopolymers; Sodium alginate; Guar gum; Sustained release; Peptic ulcer